Breakfast with Jane Austen - White, Eileen (Petits Propos Culinaires, 1994)
The author has contributed the chapter on breakfasts, ’First Things First’, to Luncheons, Nuncheons, and other Meals: Eating with the Victorians, papers from the Seventh Leeds Symposium on Food History and Traditions, edited by C Anne Wilson, to be published in the autumn of 1994 by Alan Sutton Publishing.